Benzalhydantoin derivative-based inhibitors of eight receptor tyrosine kinases: synthesis, in-vitro, and in-silico study - Muhammad Naufal,; Hidayat, Ika Wiani; Hermawati, Elvira; Syah, Yana Maolana; Al-Anshori, Jamaludin (Penerbit Universiti Kebangsaan Malaysia, 2025)
Some hydantoin derivatives have been explored for their potential as anticancer agents by inhibiting receptor tyrosine kinases (RTKs). Benzalhydantoin derivatives were obtained from a two-step reaction: condensation and alkylation reaction. The benzalhydantoin activities were obtained from the enzymatic assay, while the molecular interaction was simulated with molecular docking. Five known compounds (5-9) and two new benzalhydantoin derivatives 10-11 have been synthesized from the appropriate precursors with 4-71% yields. The structures of the compounds were determined mainly by NMR and mass spectral data. From the chemical shift of the H-7’, the configuration of the products 5, 7, 9-11 were determined as Z-isomer, while 6 and 8 were defined as E-isomer. A bioassay of the seven derivatives at 10 μM against eight receptor tyrosine kinases (EGFR, HER2, HER4, IGF1R, InsR, VEGFR-2, and PDGFR-α and -β) showed that 8:(Z)-5-(4'-hydroxy-3'methoxybenzylidene)imidazolidine-2,4-dione and 10: (Z)-5-(4'-methoxybenzylidene) imidazolidine-2,4-dione were moderately active against VEGFR-2, with inhibition of 46 and 56%, respectively. In addition, 8 was also active against PDGFR-α and -β, with a 57% inhibition. Further evaluation of 8 and 10 using AutoDock4 showed their binding energy interactions with VEGFR2 (PDB ID: 4AG8) around -6.96 and -7.32 kcal/mol, respectively. Thus, both compounds are potential candidates to be optimized further as inhibitors of angiogenesis blood vessel development.